2015
DOI: 10.1002/adma.201500335
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudo‐Regular Alternating Conjugated Copolymer Using an Asymmetric Monomer: A High‐Mobility Organic Transistor in Nonchlorinated Solvents

Abstract: Pseudo-regular alternating PDPP-TVS copolymers using an asymmetric monomer (thiophene-vinylene-selenophene (TVS)) are synthesized. Unlike regular alternating copolymers, these polymers are highly soluble in nonchlorinated solvents such as tetra-hydrofuran, toluene, xylene, and tetralin. The organic field-effect transistor devices fabricated using these polymers dissolved in nonchlorinated solvents exhibit a high hole mobility up to 8.2 cm(2) V(-1) s(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 35 publications
(44 reference statements)
1
51
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43][44][45] Of those, few were focused on improving the solubility of conjugated polymers via molecular design. 34,35,39,40,43,45 In general, three ways can be employed to increase the solubility of conjugated polymers. Foremost, the introduction of bulky side chains to the conjugated backbone can decrease the interaction between the macromolecules or increase the interaction between the polymer and the solvent, and then enhance solubility of the polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37][38][39][40][41][42][43][44][45] Of those, few were focused on improving the solubility of conjugated polymers via molecular design. 34,35,39,40,43,45 In general, three ways can be employed to increase the solubility of conjugated polymers. Foremost, the introduction of bulky side chains to the conjugated backbone can decrease the interaction between the macromolecules or increase the interaction between the polymer and the solvent, and then enhance solubility of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…47 Thirdly, the strong aggregation tendency of conjugated polymers could be suppressed by reducing regioregularity, resulting in an increase of solubility. 35,40,43,45 For example, Zhu etc. have shown that decreasing regioregularity, to some extent, may render polythiophene derivatives good solubility in o-xylene without deteriorating their organic field-effect transistor (OFET) performance.…”
Section: Introductionmentioning
confidence: 99%
“…[3] While many conjugated polymers have shown high hole/electron mobility, [4] the study of conjugated polymers with ambipolar charget ransport has been lagged behind. The polymers exhibit extra-low band gap with energy levels closet oÀ4.0 eV and À5.0 eV due to the strong electron-donating and withdrawing ability of porphyrin and diketopyrrolopyrrole.…”
mentioning
confidence: 99%
“…[3] While many conjugated polymers have shown high hole/electron mobility, [4] the study of conjugated polymers with ambipolar charget ransport has been lagged behind. [1] Solution-processed conjugated polymers with high molecular weight and viscosity are able to apply into roll to roll printing technique, providing the advantage to realize large-area flexible OFET devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation